Protective influence of Costus afer Aqueous Extract In Rats Fed With Crude Oil Contaminated Diet as Measured by Employing Biochemical Indices - Mordi, Joseph C; Achuba, Fidelis Ifeakachuku; Ichipi-Ifukor, Patrick Chukwuyenum; Emete, Gift; Mokogwu, Azukaego Thomas Hughs; Nmanedu, Abigail Chioma; Aruoren, Oke; Ohwokevwo, Oghenenyore Andy (Iraqi Journal of Science, 2021)
The use of medicinal plants in the treatment of harmful impacts of xenobiotics in animals is attracting an increasing attention in recent times. The aim of the current study is to assess the preventive potential of Costus afer aqueous leaves extract (CAAE) in treating metabolic aberrations imposed by crude oil contaminated diet inWistar albino rats. Six groups of rats were treated as follows: A = Normal diet; B=Normal diet + 100 mg/kg body weight of CAAE; C =Normal diet + 200 mg/kg body weight of CAAE; D= Crude oil contaminated diet; E= crude oil contaminated diet + 100 mg/kg body weight of CAAE, F = crude oil contaminated diet + 200 mg/kg body weight of CAAE. After thirty days of exposure to the diet and administration of the corresponding plant extracts, the rats were sacrificed with chloroform and the required organs were excised. The hematological indices, as well as function indicators and levels of drug metabolizing enzymes in the liver and kidney, were investigated with standard protocols. The results indicated that the hematological parameters and kidney and liver function indices were altered in rats fed with crude oil contaminated diet. However, the values came close to those in control rats when Costus afer aqueous extracts were administered. Similarly, the activities of oxidase enzymes (aldehyde oxidase, monoamine oxidase, xanthine oxidase, and sulphite oxidase), following their inhibition by the ingestion of crude oil contaminated diet, equally restored close to control values upon treatment with Costus afer aqueous extract. This study, therefore, was able to establish an aqueous extract of Costus aferleave as an antidote for crude oil intoxication.